1993
DOI: 10.1164/ajrccm/148.5.1411
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Forceps Size on the Adequacy of Specimens Obtained by Transbronchial Biopsy

Abstract: This study prospectively compared the diagnostic yield of transbronchial biopsies using large and small forceps (cup sizes, 3 x 2 x 0.9 versus 2 x 1.5 x 0.6 mm, respectively). Diagnostic yield was compared by a pathologist, blinded to the size of forceps used on the basis of the relative amount of tissue obtained, alveolar tissue obtained, and ability to ascertain a histopathologic diagnosis. Large forceps obtained significantly more tissue than did small forceps (20 of 27 patients [74%] versus five of 27 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 6 publications
0
19
1
2
Order By: Relevance
“…Specimens that floated were no more likely to be diagnostic or abnormal than specimens that sank (p < 0.05). Loube et al [59]prospectively compared the diagnostic yield of transbronchial biopsies using large and small forceps (cup sizes, 3 × 2 × 0.9 vs. 2 × 1.5 × 0.6 mm, respectively). Large forceps obtained significantly more tissue than did small forceps [20 of 27 patients (74%) vs. 5 of 27 patients (19%), p < 0.005].…”
Section: Immunocompetent Subjectsmentioning
confidence: 99%
“…Specimens that floated were no more likely to be diagnostic or abnormal than specimens that sank (p < 0.05). Loube et al [59]prospectively compared the diagnostic yield of transbronchial biopsies using large and small forceps (cup sizes, 3 × 2 × 0.9 vs. 2 × 1.5 × 0.6 mm, respectively). Large forceps obtained significantly more tissue than did small forceps [20 of 27 patients (74%) vs. 5 of 27 patients (19%), p < 0.005].…”
Section: Immunocompetent Subjectsmentioning
confidence: 99%
“…(Prakash at al., 1991;American Thoracic Society [ATS], 1987) A comparison of the yield of transbronchial biopsy specimen between standard-sized forceps and large forceps found no significant differences in the size of the biopsies or in the amount of alveolar tissue collected. (Wang et al, 1980;Loube et al, 1993) The tissue samples obtained by means of TBBx forceps are small, approximately 3 mm in size. Therefore, this procedure is not useful in diagnosing heterogeneous lung diseases such as idiopathic lung diseases.…”
Section: Transbronchial Biopsy (Tbbx)mentioning
confidence: 99%
“…(Papin et al, 1985;Zavala, 1976;Borchers & Beamis 1996) The risk of bleeding during TBBx seems to be unrelated to the size of forceps and is slightly higher in those being mechanically ventilated. (Loube et al, 1993;O'Brien et al, 1997) In patients with a potential increased risk of bleeding, coagulation profile should be checked before bronchoscopy. There is no information about what constitutes a "safe" level for clotting in this context.…”
Section: Bleeding Complicationsmentioning
confidence: 99%
“…However, one of the limiting features of this technique is the small sample obtained using conventional forceps [1]. Previous studies have suggested that larger forceps may improve diagnostic yield; however, as forceps become larger, there is greater concern about the development of complications, particularly bleeding [2,3,4]. In recent years, larger forceps connected to an electrocautery system, named the ‘hot forceps’, were designed for use with flexible bronchoscopy.…”
Section: Introductionmentioning
confidence: 99%